1987
DOI: 10.1002/hrm.3930260105
|View full text |Cite
|
Sign up to set email alerts
|

Human Resources Management Innovation

Abstract: Guided by a general manager's perspective of human resources management (HRM), this paper identifies key factor affecting the introduction of HRM innovations in organizations. Because the essence of market and technological leadership is the development of the organizational capacity to carry out inventive ideas, it is critical to understand the main forces influencing HRM innovation. Following a definition of HRM innovation, six propositions are discussed using current and historical examples. Since HRM innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 16 publications
2
55
0
3
Order By: Relevance
“…Second, the findings of this study expand on Kossek's theory of HRM innovation (Kossek, 1987). Kossek assumed that success or failure in previous attempts affected targeted users' perceptions of new practices, influencing their subsequent efforts in relation to innovation.…”
Section: A Theoretical and Research Implicationssupporting
confidence: 59%
“…Second, the findings of this study expand on Kossek's theory of HRM innovation (Kossek, 1987). Kossek assumed that success or failure in previous attempts affected targeted users' perceptions of new practices, influencing their subsequent efforts in relation to innovation.…”
Section: A Theoretical and Research Implicationssupporting
confidence: 59%
“…Because of the possibility of substituting higher wages for investments in human resource practices, it could be argued that a measure of compensation offered by the business unit should be included in the estimated models as a control variable. On the other hand, organizations that invest relatively more in human resource practices will likely offer higher wages than those that invest less (for example, it has been empirically demonstrated that large firms both pay higher wages and make greater average investments in human resource programs than smaller organizations (Ehrenberg, 1990;Kossek, 1987)). In this case, wages and human resource management practices will be positively correlated.…”
Section: Limitationsmentioning
confidence: 97%
“…There is also plenty of research work on specific aspects of management innovation implementation (Kossek 1987;Nickell et al 2001;McCabe 2002;Hargrave & Van de Ven 2006) and some research work about the effects of management innovations on the adopting organizations (Biagi et al 2008;Bryson et al 2009). At the same time, management innovation research work on the company level is quite rare.…”
Section: Management Innovation -The Modelmentioning
confidence: 99%